The impact of a school-based gardening intervention on intentions and behaviour related to fruit and vegetable consumption in children. (June 2015) - Duncan, Michael J; Eyre, Emma; Bryant, Elizabeth; Clarke, Neil; Birch, Samantha; Staples, Victoria; Sheffield, David
A total of 77 children (34 boys, 43 girls, mean age ± standard deviation = 9 ± 1 years) participated in this study; 46 children (intervention) undertook a 12-week school gardening programme and 31 children acted as controls. Measures of the Theory of Planned Behaviour and fruit and vegetable consumption were taken pre- and post-intervention. Repeated measures analysis of variance and hierarchical regression analysis indicated that the intervention group increased daily consumption of fruits and vegetables and increased intentions, attitudes, norms, and perceived behavioural control related to fruit and vegetable consumption. Attitudes, norms and perceived behavioural control significantly predicted changes in fruit and vegetable consumption.